Jordan : 2022 Article IV Consultation and Fourth Review Under the Extended Arrangement Under the Extended Fund Facility, Request for Augmentation and Rephasing of Access, and Modification of Performance Criteria-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Jordan. (IMF Staff Country Reports; Country Report ;, 2022)
The economy started to recover in 2021-with growth, fiscal performance, and the current account outperforming program expectations. Inflation remained subdued in 2021, but has picked up in recent months. Growth is expected to strengthen to 2.4 percent in 2022, but is being marked down by 0.3 ppts. from the third review, reflecting global economic headwinds, including tighter financial conditions and spillovers from the war in Ukraine. Although Jordan's wheat reserves provide assurance on near-term food security, persistently high food and fuel prices pose a major near-term policy challenge, especially given high unemployment (23 percent) and limited fiscal space. The current account deficit is projected to widen to 6.7 percent of GDP in 2022, as a larger fuel import bill dominates strong tourism receipts and robust exports.